Pelatihan Pembuatan Preparat Basah dan Kering Tumbuhan Berbasis Kearifan Lokal di SMAS Pelita Karya: Training in Making Wet and Dry Plant Preparations Based on Local Wisdom at SMAS Pelita Karya - Kamaluddin, Kamaluddin; Siahaan, Desta Gloria; Manalu, Adelya Irawan; Pardosi, Lukas (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
This community service aims to provide training to teachers and students of SMAS Pelita Karya in making wet and dry plant preparations based on local wisdom. This activity was motivated by the lack of laboratory facilities and the limited ability of teachers to carry out effective biology practicums. The training was carried out using the In-Service Training (IST) and On-Service Training (OST) methods involving science teachers and students. The results of this activity showed an increase in the competence of teachers and students in making and utilizing wet and dry preparations from local plants for biology practicum activities. In addition, there was an increase in students’ understanding of biological concepts through the use of contextual and relevant preparation media to their surroundings. This activity concludes that training in making preparations based on local wisdom can improve the quality of biology learning at SMAS Pelita Karya and enrich learning methods based on local resources.